Annotated record of the detailed examination of Mn deposits from the 1993 R/V Sonne SO-80a expedition in the Pacific Ocean - Peter Stoffers; Roger Hekinian (PANGAEA, 1992)
SONNE 80a was a multidisciplinary expedition to map and sample intraplate volcanic activity associated with the proposed Easter "hotline" and its relation to the Orongo Transform Fault. The main objectives of the cruise were: 1) to study the area between Easter island, the Orongo Transform Fault and the East Pacific Rise (EPR), in particular to examine the relationship between near-spreading axis and true intraplate volcanic processes. 2) to study the Orongo Transform Fault (probably a "leaky transform") which forms the southern boundary of the of the Easter microplate, to determine to what extent it is involved in the Easter "Hotline" volcanism. 3) to examine the proposed extension of the Easter "hotline" to the west of the EPR in the direction of Henderson, Ducie and Crough Seamounts.